RESULTS OF TREATMENT OF ACUTE IDIOPATHIC SCROTAL EDEMA IN CHILDREN - Firdavs Mukhitdinovich Tukhtaev; Farkhod Shavkatovich Mavlyanov; Shavkat Khojamkulovich Mavlyanov (Research Focus International Scientific Journal, 2024)
Acute diseases of the scrotal organs are a serious problem in children and are a common cause of emergency hospitalization. Edematous scrotum syndrome can be caused by various causes that exhibit similar clinical symptoms, which complicates differential diagnosis. Currently, there is no clearly defined algorithm of action for children who are urgently hospitalized with edematous scrotum syndrome. Nevertheless, in the presence of anamnesis and clinical signs that do not exclude testicular torsion, it is urgently necessary to conduct a surgical revision without additional examination methods.